THE APPLICATION OF GUIDED DISCOVERY LEARNING MODEL TO IMPROVE STUDENTS’ CRITICAL THINGKING ABILITY AT THE EIGHTH GRADE STUDENTS’ OF MTs AL-HUDA PEKANBARU - Arif Fadillah; Yennita Yennita; Muhammad Sahal (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
Critical thinking is one of the high-level thinking stages that can be interpreted as a process of thinking precisely, directed, reasoned, and reflective in decision-making that can be trusted. This study was aimed to determine the improvement of critical thinking skills toward Guided Discovery Learning model of grade VIII students at MTs Al-Huda Pekanbaru on light material. The type of research used was experimental research. Descriptive analysis was used to analyze the data. This analysis gave the description about influence of Guided Discovery Learning model toward student's critical thinking ability. The subjects of this study were 58 students. The data was collected based on critical thinking skill's test result which consisted of 15 essay questions for 5 indicators after Guided Discovery Learning model was applied on experiment class and conventional model on control class. Mean score of sudents' critical thinking ability on experiment class was 78.45 which was in a high category and average score of students' critical thinking skill on control class was 70.52 which was in low category. Based on the result of students' critical thinking skill, it can be concluded that there was an improvement of critical thinking ability after guided discovery learning model was applied by 11.24% compared to conventional learning model.